2005
DOI: 10.1093/molehr/gah134
|View full text |Cite
|
Sign up to set email alerts
|

Maternal genetic polymorphisms in CYP1A1, GSTM1 and GSTT1 and the risk of hypospadias

Abstract: Hypospadias is one of the most common congenital anomalies. Increased exposure to environmental factors (endocrine-disrupting chemicals and smoking) or maternal endogenous estrogen may cause hypospadias because male sexual differentiation is dependent on normal androgen homeostasis. Moreover, interactions between genetic factors and cigarette smoking and other chemicals have been suggested. It has been demonstrated that the CYP1A1 metabolizes not only environmental chemicals but also estrogens, and glutathione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 43 publications
2
34
1
Order By: Relevance
“…Genetic polymorphisms in these transcription factors and enzymes may be important in determining individual susceptibility to EED exposure and also in the development of MGMs. [13][14] Both our study, and other previous studies have identified that genetic variants for ESR1 and ESR2 could raise the susceptibility of CO and HS by enhancing the effects of estrogenic EEDs, which are known as xenoestrogens and currently the largest group of known EEDs. 7,15 In addition, several nuclear receptors, such as aryl-hydrocarbon receptor (AHR) and pregnane X receptor (PXR or NR1I2), are known to be crucial for EED-mediated CYP transcription.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Genetic polymorphisms in these transcription factors and enzymes may be important in determining individual susceptibility to EED exposure and also in the development of MGMs. [13][14] Both our study, and other previous studies have identified that genetic variants for ESR1 and ESR2 could raise the susceptibility of CO and HS by enhancing the effects of estrogenic EEDs, which are known as xenoestrogens and currently the largest group of known EEDs. 7,15 In addition, several nuclear receptors, such as aryl-hydrocarbon receptor (AHR) and pregnane X receptor (PXR or NR1I2), are known to be crucial for EED-mediated CYP transcription.…”
Section: Introductionsupporting
confidence: 62%
“…CYP1A2 variants are in linkage disequilibrium with CYP1A1 alleles, which themselves have been previously associated with the risk of infertility and HS. 13 Moreover, CYP1A1 and CYP1A2 share many of the same enzymatic activities and may be under coordinated regulation; placental expression and activity of CYP1A1 seem to be greater than for CYP1A2 and to occur earlier in pregnancy. 41 However, we did not find any positive CYP1A1 variants in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Because we had observed an association between prenatal dioxin levels and AHR and CYP1A1 genotypes [14] and between prenatal smoking and maternal AHR, CYP1A1 and GSTM1 genotypes and reduced birth weight [22,31], we evaluated those three genetic polymorphisms in the present study. The AHR (G>A, rs2066853) and CYP1A1 (T>C, rs4646903) polymorphisms were determined using PCR [32,33]. GSTM1 null and non-null genotypes were determined using multiplex PCR [30,32].…”
Section: Genetic Analysesmentioning
confidence: 99%
“…The QIAamp DNA Blood Mini Kit (QIAGEN GmbH, Hilden, Germany) [30] and Maxwell 16 DNA Purification Kit (Promega, Madison, WI, USA) were isolate and purify DNA according to the manufacturer's instruction. AHR, CYP1A1, CYP1A2, CYP1B1, GSTM1 (+/-), and GSTT1 (+/-) polymorphisms were determined by the TaqMan PCR method as described [11,[31][32][33][34][35]. XRCC1 genotyping was performed using a 7300/7500 Real-Time PCR AmpErase UNG (Applied Biosystems) in a total volume of 10 µL.…”
Section: Genotype Measurementsmentioning
confidence: 99%